HUBUNGAN ANTARA KECANDUAN GAME DENGAN PERILAKU AGRESIF VERBAL PADA USER GAME ONLINE - Safitri, Sekar; Fikri (Jurnal Bimbingan dan Konseling Pandohop, 2022)
This study aims to determine the relationship between game addiction and verbal aggressive behavior in online game users. The hypothesis of this research is that there is a relationship between game addiction and verbal aggressive behavior in online game users. The method used is a quantitative approach with a correlational design and the subject-taking technique in this study uses a purposive sampling technique, with the criteria of individuals being in the stage of adolescence to early adulthood (12 years to 40 years) playing online games; has a minimum playing time span of more than 3-5 hours day, the type of game is MMORPG, MOBA, FPS, Battle Royale as many as 174 people. The scale used for data collection is a game addiction scale with an item power range of 0.280-0.611 and has a reliability value of Cronbach's alpha of 0.929 and a verbal aggressive scale with an item power range of 0.300-0.674 and has a reliability value of Cronbach's alpha of 0.945. Analysis of the data used is Pearson's product moment correlation with the help of SPSS 23.0 (Statistical Packages for the Social Sciences) software. The results of statistical calculations show the correlation value (r = 0.639; p < 0.05). These results indicate that there is a positive relationship between game addiction and verbal aggressive behavior in online game users.